(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the impact of globalization processes on the spiritual worldview of the younger generation, threats in the modern information space, and pedagogical and social mechanisms for the spiritual protection of children. The importance of family upbringing, educational institutions, and public cooperation is also scientifically highlighted. In addition, the impact of globalization processes on the spirituality of young people, threats under the guise of "mass culture" and pedagogical and social measures to protect the younger generation from them are analyzed.